Financial Stability In The Eurozone - Zielińska, Klaudia (Comparative Economic Research. Central and Eastern Europe, 2016)
Financial stability inside the European Monetary Union (EMU) is a trendy topic in most developed countries around the world. From the moment the EMU was brought to life, there was much speculation about its imperfections, inadequate management, and vulnerability. Some of them have turned out to be true, while others have been proved invalid. Nevertheless, the debt crisis has demonstrated inadequacies in the EMU’s structure and proved that a higher degree of integration is necessary in order to guarantee the robustness of the common currency and fully utilize its potential. This article summarizes the most serious doubts with respect to the functioning of the monetary union and evaluates their credibility over time. New financial stability-securing solutions are also described and analyzed as to whether they are sufficient to prevent Europe from stumbling from one crisis to another. The subject is analyzed over different periods of time – firstly describing the term “financial stability”, along with the major concerns about the process of introducing the euro at the time of its finalization and implementation. Secondly the article describes how these preceding doubts have been verified during the following fourteen years of the EMU’s functioning. The revealed weaknesses of the EMU are also underlined in order to prove the need of further integration. The final section summarizes the solutions implemented in response to the crises that have hit Europe during the time of the Euro’s functioning.